2018
DOI: 10.1055/s-0043-121888
|View full text |Cite
|
Sign up to set email alerts
|

Körperliche Aktivität im Kontext der betrieblichen Gesundheitsförderung – ein systematisches Review zur Effektivität software- gegenüber personalgestützter Interventionen

Abstract: This paper demonstrates that positive effects can be achieved with both intervention types. Software-based interventions show advantages due to the use of new technologies. Use of desktop or mobile applications facilitate organization, communication and data acquisition with fewer resources needed. A schooled trainer, on the other hand, is able to react to specific and varying needs of the employees. This aspect should be considered as very significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Previous interventions to promote PA in the workplace are often more formalised and based on a fixed course structure with longer sessions (eg, 3×50 min of yoga per week, 2 hours of fitness training in leisure time, 30–60 min of fitness training once a week, weekly yoga and fitness classes 23 ), which take place at a fixed time in a fixed place. However, new challenges for the working environment, such as digitalisation, working from home and the COVID-19 pandemic, require interventions independent of location and time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous interventions to promote PA in the workplace are often more formalised and based on a fixed course structure with longer sessions (eg, 3×50 min of yoga per week, 2 hours of fitness training in leisure time, 30–60 min of fitness training once a week, weekly yoga and fitness classes 23 ), which take place at a fixed time in a fixed place. However, new challenges for the working environment, such as digitalisation, working from home and the COVID-19 pandemic, require interventions independent of location and time.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the intervention period is 5 weeks, a relatively short period for PA interventions in the workplace. 23 However, to test the effects of the intervention, the duration seems acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Im Unterschied zu medizinischen Eingriffen konzentrieren sich verhaltensbezogene Maßnahmen meist auf Prävention in den Bereichen Ernährung, Bewegung, Entspannung bzw. Stress und Sucht [14] und werden meist als personal-oder softwaregestützte Intervention angeboten [15]. Angebote umfassen bspw.…”
Section: Anwendbarkeit Außerhalb Des Arzt-patient-verhältnissesunclassified
“…Workplace exercise interventions may increase PA levels (11). Nevertheless, it remains uncertain whether they also have a positive impact on health (12,13). Observational studies showed that leisure time PA positively affects health.…”
Section: Introductionmentioning
confidence: 99%